Social Communication To Improve Psds Adoption at Syariah Pawnshops Using Atlas.Ti - Oktaviani, Indah; Idwal B, Idwal B; Sumarni, Yenti (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose:This study aims to analyze the role of social communication in increasing the adoption of the Pegadaian Syariah Digital Service (PSDS) application to support the effectiveness of services at the Pegadaian Syariah Bengkulu Branch. The low use of the PSDS application by customers is the reason for the importance of this study, it is hoped that the results can provide recommendations for more effective communication strategies. Methodology:This study uses a qualitative descriptive approach. Data were collected through observation, in-depth interviews with 10 informants (employees and customers), and documentation. Data analysis was carried out with the help of Atlas.ti software for thematic coding and interpretation. Results: The findings show that direct interaction between employees and customers is the most effective communication channel compared to social media. The PSDS application has been proven to increase service efficiency, but still faces obstacles such as system errors and limited understanding of technology by customers. Findings:Social communication strategies can increase awareness, understanding, and adoption of applications. Recommendations from the social environment also play an important role. Novelty:This study combines social communication analysis and the use of Atlas.ti software to reveal the effectiveness of sharia-based digital services. Originality:This study provides a new perspective on the importance of a social communication approach in driving the adoption of digital financial services at the local level. Conclusion: Empirical research paper. Type of Paper:Research articles.